Cetacean rapid assessment: An approach to fill knowledge gaps and target conservation across large data deficient areas. Issue 1 (5th October 2017) - Braulik, Gill T.; Kasuga, Magreth; Wittich, Anja; Kiszka, Jeremy J.; MacCaulay, Jamie; Gillespie, Doug; Gordon, Jonathan; Said, Said Shaib; Hammond, Philip S.
Abstract: Many species and populations of marine megafauna are undergoing substantial declines, while many are also very poorly understood. Even basic information on species presence is unknown for tens of thousands of kilometres of coastline, particularly in the developing world, which is a major hurdle to their conservation. Rapid ecological assessment is a valuable tool used to identify and prioritize areas for conservation; however, this approach has never been clearly applied to marine cetaceans. Here a rapid assessment protocol is outlined that will generate broad‐scale, quantitative, baseline data on cetacean communities and potential threats, that can be conducted rapidly and cost‐effectively across whole countries, or regions. The rapid assessment was conducted in Tanzania, East Africa, and integrated collection of data on cetaceans from visual, acoustic, and interview surveys with existing information from multiple sources, to provide low resolution data on cetacean community relative abundance, diversity, and threats. Four principal threats were evaluated and compared spatially using a qualitative scale: cetacean mortality in fishing gear (particularly gillnets); cetacean hunting, consumption or use by humans; shipping related collision risk and noise disturbance; and dynamite fishing. Ninety‐one groups of 11 species of marine mammal were detected during field surveys. Potentially the most important area for cetaceans was the Pemba Channel, a deep, high‐current waterway between Pemba Island and mainland Africa, where by far the highest relative cetacean diversity and high relative abundance were recorded, but which is also subject to threats from fishing. A rapid assessment approach can be applied in data deficient areas to quickly provide information on cetaceans that can be used by governments and managers for marine spatial planning, management of developments, and to target research activities into the most important locations.